Integration process simulator: A tool for performance evaluation of task scheduling of integration processes - Freire​, D. L.; Frantz, R. Z.; Roos-Frantz, F.; Basto-Fernandes, V. (Journal of Simulation, 2022)
Due to large volumes of data from Cloud Computing and from the Internet of Things, the companies’ software ecosystem requires an efficient integration of applications and services. Performance improvement from integration platforms’ runtime systems is directly related to task scheduling strategies from integration processes. It is still a challenge to find the proper heuristic for a given integration process subject to high inbound data rates. This article proposes a simulation tool for the field of Enterprise Application Integration, which implements different scheduling heuristics and allows the extraction of performance metrics. Three task scheduling heuristics were simulated during the integration process, and the results were evaluated through statistical tests.